Bridging and Bounding Social Capital: Social Interaction Analysis of Islets Islanders in Wakatobi Marine National Park - La Ola, Taane; Wianti, Nur Isiyana; Tadjuddah, Muslim (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2020)
The purpose of this paper is to provide an overview of the differences in the strength of social capital that is bonding and bridging two community groups, namely land-dwellers and Sama Bajo boat-dwellers in three islands in Wakatobi Marine National Park. This study used a post-positivistic research paradigm, and the primary data were collected by using a questionnaire to 240 respondents who represented the group of land-dwellers and Sama Bajo boat-dwellers on the islands of Wangi-wangi, Kaledupa, and Tomia. This research was also supported by qualitative data through in-depth interviews from several informants and desk studies. The results showed that bridging social capital relations tend to be weak in the two forms of interactions between the Sama Bajo and the land-dwellers on Wangi-wangi Island and Kaledupa Island, while bridging social capital tend to be secured in Tomia Island. We found that the social context through the historical links in the past and identity played a role in the relationship of bridging social capital and bonding social capital in the three communities as an analytical unit of this research.